2020
DOI: 10.3168/jds.2019-17457
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Enhanced autophagy activity in liver tissue of dairy cows with mild fatty liver

Abstract: During the transition period, dairy cows are challenged by increased energy demands and decreased dry matter intake, which can induce a variety of metabolic disorders, especially fatty liver. Dairy cows suffering from mild or moderate fatty liver in this period show no distinct clinical symptoms, indicating the occurrence of adaptive processes. The process of autophagy (an adaptive response) leads to degradation of intracellular components to generate energy and maintains cellular homeostasis during negative n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Our results indicate that NEFA can promote the protein expression of ATG7, p62, BECN1, and LC3-II in hepatocytes and increase the number of autophagosomes ( Figure 3 and Figure 4 ), which clearly demonstrates that NEFA promotes autophagosome formation in hepatocytes. In line with our results, Chen et al indicated that enhanced formation and degradation of autophagosomes were found in the liver of cows with mild fatty liver during the perinatal period [ 15 ]. Moreover, Li et al previously suggested that activation of autophagy and an increase in the number of autophagosomes were found in the mammary tissues of cows with hyperketonemia [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that NEFA can promote the protein expression of ATG7, p62, BECN1, and LC3-II in hepatocytes and increase the number of autophagosomes ( Figure 3 and Figure 4 ), which clearly demonstrates that NEFA promotes autophagosome formation in hepatocytes. In line with our results, Chen et al indicated that enhanced formation and degradation of autophagosomes were found in the liver of cows with mild fatty liver during the perinatal period [ 15 ]. Moreover, Li et al previously suggested that activation of autophagy and an increase in the number of autophagosomes were found in the mammary tissues of cows with hyperketonemia [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Autophagy is a catabolic process in which the damaged cytoplasmic organelles or cytosolic components are degraded by lysosomal proteases, and it can contribute to modulating lipid metabolism by directly regulating lipid degradation [ 13 , 14 ]. A number of previous studies have shown that dairy cows with mild fatty liver show a more active lipid metabolism and enhanced autophagy, which serve as adaptive mechanisms of dairy cows during the perinatal period [ 15 , 16 ]. Therefore, when the liver is exposed to a high blood concentration of NEFA, autophagy plays an important role in maintaining the stability of hepatocytes, thereby providing nutrients and alleviating lipid accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…In dairy cows, autophagy is altered during metabolic disorders in the transition period. Enhanced autophagic activity in the liver and mammary gland has been associated with response mechanisms to alleviate metabolic stress induced by mild fatty liver and hyperketonemia (Chen et al, 2020;Li et al, 2020). At least in nonruminants experiencing metabolic disorders associated with adipose tissue dysfunction, autophagy is stimulated by oxidative stress (Zhang et al, 2012;Mizunoe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing activity of mTORC1 inhibited ATGL abundance in epididymal fat of mice (Chakrabarti et al, 2013). Although our previous work has indicated that autophagy was an important biological mechanism in cows with fatty liver (Du et al, 2018;Chen et al, 2020), the potential role of autophagy in the lipolytic response during the peripartal period is unknown.…”
Section: Introductionmentioning
confidence: 98%